Cognitive assistance systems for manual assembly throughout the German manufacturing industry - Klaus Fink (Journal of Applied Leadership and Management, 2020)
Research questions: Do the main German manufacturing industries use cognitive assistance systems in their manual assembly as described theoretically in literature? Methods: For collecting primary data, an online survey was conducted and data from 68 representatives within the main German manufacturingindustries was used for measuring the targets for and effects of their usage of cognitive assistance systems in the context of social economics, learnings aspects, quality and productivity improvements. Results: The analysis shows that cognitive assistance systems are utilized in the main German manufacturing industries with a statistical probability for increasing the stability of processes within manual assembly. Moreover, cognitive assistance systems seem to be used for the alignment and documentation of finished assembly steps, such as screwing, helping workers avoid mistakes in the execution of tasks and slips of memory or faulty reasoning in recalling previousprocesses. Finally, this study detects an urgent need for improvements in the automotive industry, especially in manual assembly, for process descriptions.
Keywords: 650